Competent Forum and Applicable Law in Personal Data Protection with a Foreign Element - Adhiwisaksana, Muhammad Faqih; Allagan, Tiurma Mangihut Pitta (Indonesian Journal of International Law, 2023)
This research analyses on personal data protection with a foreign element as a private international law issue, focusing on competent forum and applicable law. The author uses a juridical-normative research method with literature studies to explain the relevant private international law principles, as well as Indonesian laws and regulations surrounding competent forum and applicable law regarding competent forum and applicable law on personal data protection with a foreign element. The study found that various private international law principles may be used to determine the applicable law in personal data protection with a foreign element dispute, such as nationality, place where the tort occurred, or center of gravity. Indonesian courts are also competent to examine personal data protection with a foreign element case under Indonesian law. This study also elaborates practical implementation personal data protection with a foreign element, in particular on the competent forum and applicable law, as shown in the businesses Intercompany Agreement on Data Processing by X group company and in a cross-border acquisition transaction.